2022
DOI: 10.3201/eid2801.211543
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Infections Caused by Kazachstania spp., Strasbourg, France, 2007–2020

Abstract: Emergence might be associated with increasing immunocompromised conditions and gastroesophageal diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…K. telluris is an opportunistic yeast that can cause fungemia in humans. This particular yeast is frequently confected with C. albicans [ 39 ]. In the present study, we found K. telluris colonized in the pigeon excreta at a rate of approximately 4.77%.…”
Section: Discussionmentioning
confidence: 99%
“…K. telluris is an opportunistic yeast that can cause fungemia in humans. This particular yeast is frequently confected with C. albicans [ 39 ]. In the present study, we found K. telluris colonized in the pigeon excreta at a rate of approximately 4.77%.…”
Section: Discussionmentioning
confidence: 99%
“…Albeit rare, Syphacia sp. can infect humans and is a zoonotic parasite [ 69 , 70 ]. Heligmosomoides sp.…”
Section: Discussionmentioning
confidence: 99%
“…A single-center French study identified 13 cases of Kazachstania spp. infection expanding over 14 years, three of which qualified for invasive disease [ 75 ]. Two other cases of invasive disease had been reported earlier.…”
Section: Introductionmentioning
confidence: 99%
“…Two other cases of invasive disease had been reported earlier. The infection has been observed in immunocompromised individuals, and identification of the fungi is performed using MALDI-TOF and ITS sequencing [ 75 ].…”
Section: Introductionmentioning
confidence: 99%